TZO target sintering forming process
Through the TZO target sintering molding process, including spray molding agent and multi-stage hot press sintering, the TZO target density and stability problems are solved, and high-density and high-performance TZO target materials are achieved, suitable for vacuum evaporation.
Patent Information
- Application Number
- CN202411322688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The density of TZO targets is difficult to achieve higher during the production process, especially in the structural stability and compactness of the special-shaped target materials, and are prone to residual rates and disintegration, especially in automated production.
A TZO target sintering molding process is adopted, including powder mixing, embryo molding, shaping, pre-sintering, sintering, calcining and heat treatment steps. By spraying molding agent, zinc oxide powder and tin oxide powder are fully mixed, static pressure is used to form a stable structure, and Heat pressing and sintering are performed at different temperatures and pressures to ensure complete fusion and combination of the material.
It improves the structural stability and compactness of the TZO target, avoids cracking and damage, significantly improves density and conductive properties, is suitable for vacuum evaporation, and enhances its application performance in the electronics industry.
Smart Images

Figure BDA0005054446230000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic products, and more specifically, to a TZO target sintering molding process. Background Art
[0002] As the scale and requirements of the electronics industry, especially integrated circuits, optical discs and flat panel displays, continue to increase.
[0003] TZO target is a target material made of tin oxide powder (ZnO: SnO2). It is widely used in the electronics industry because of its high transparency, tactile responsiveness, and conductivity. TZO targets need to go through static pressing, sintering and other processes during production, and some are formed by melt casting and forging. The density of TZO targets produced by the current process is 5.5-6.3.
[0004] Moreover, TZO is compacted by very high pressure during the static pressing process, but it is difficult to achieve a higher density; especially for special-shaped targets, the structural stability and density are difficult to control during the production and molding process, especially in the automated production process, which is prone to residual rate and collapse; further research is needed for this. Summary of the invention
[0005] In order to further improve the density of the TZO target and avoid cracking, breakage and the like during the sintering process, the present application provides a TZO target sintering molding process.
[0006] The present application provides a TZO target sintering molding process, comprising the following steps: 1) Powder mixing: weigh zinc oxide powder and tin oxide powder according to parts by weight and mix them evenly, then spray a molding agent to fully mix the molding agent with the zinc oxide powder and the tin oxide powder to obtain a mixture A; 2) Molding: subjecting the mixture A to static pressure molding to obtain a molded embryo; 3) Shaping: hot pressing the molded embryo at 105-120°C and a pressure of 10-30MPa to obtain a shaped embryo; 4) Pre-sintering: pre-sinter the shaped embryo at a temperature of 280-305°C for 10-30 minutes, and hot press to obtain a pre-sintered embryo; 5) Sintering: pre-sintering the pre-sintered embryo at a temperature of 1170-1200°C for 10-30 minutes to obtain a sintered embryo; 6) Calcination: sintering the sintered embryo at a temperature of 1700-1800°C for 2-3 hours, cooling, and obtaining a calcined embryo; 7) Heat treatment: After the calcined embryo is heat treated, it is ground, bound, and polished to obtain a TZO target.
[0007] The above process is simple to operate and has high production efficiency; specifically, the molding agent is a solution with good dispersibility and adhesion stability, which can coat the surface of zinc oxide powder and tin oxide powder, making it easy to adhere and form. By spraying the molding agent on zinc oxide powder and tin oxide powder during the mixing process, the zinc oxide powder and tin oxide powder are fully mixed and uniformly under the action of the molding agent, which is convenient for subsequent molding to form an embryo; and the mixture A is formed into a stable structure by static pressure molding, during which the desired shape is formed, such as special-shaped, prismatic, plate-shaped and tube-shaped. In this application, the tube shape is formed first, which is convenient for subsequent vacuum sputtering to form a TZO film with good stability and good conductivity.
[0008] In step 3), the molded embryo is hot pressed at 105-120°C and a pressure of 10-30MPa. At this temperature, part of the solvent in the embryo can be removed and further hot pressed during the process to form a stable tubular structure, and further improve the density of the structure, so that the final target material has a higher density.
[0009] In step 4), pre-sintering is performed at a temperature of 280-305° C. for 10-30 minutes. At this time, most of the setting agent has been dispersed. Maintaining a certain pressure during this process can further improve the density of the structure.
[0010] In step 5), the pre-sintered embryo is pre-sintered at a temperature of 1170-1200° C. for 10-30 minutes, at which time the zinc oxide powder begins to dissolve and is in a semi-molten and semi-solid state.
[0011] In step 6), calcination is carried out at 1700-1800°C for 2-3h, at which time, the zinc oxide powder and the tin oxide powder are completely fused and reacted to form zinc tin oxide. After the heat treatment in step 7), the density, structural stability and mechanical properties of the compound material are further improved.
[0012] In summary, the present application sequentially undergoes the processes of powder mixing, embryo molding, shaping, sintering, calcining, and heat treatment to form a TZO target with high structural stability and density, and is used in vacuum evaporation to further improve its performance.
[0013] Preferably, the specific process of step 1) is as follows: weigh zinc oxide powder and tin oxide powder and stir them at a speed of 100-150r / min for 10-20min, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, continue stirring for 20-30min, so that the zinc oxide powder, tin oxide powder and the molding agent are fully mixed to obtain a mixture A.
[0014] In the above stirring speed and stirring time range, zinc oxide powder and tin oxide powder can be easily molded, thereby improving the density of the TZO target.
[0015] Preferably, the weight ratio of zinc oxide powder, tin oxide powder and forming agent in step 1) is (5-10): (5-10):1.
[0016] By adopting the above weight ratio range, the zinc oxide powder, the tin oxide powder and the molding agent can be easily mixed and uniformly mixed, and molding can be easily performed.
[0017] Preferably, the particle size of the zinc oxide powder and the particle size of the tin oxide powder are both 50-500 nm.
[0018] The zinc oxide powder and tin oxide powder within the above particle size range can be fully mixed and evenly mixed, and are easy to shape. After being formed, they are not prone to collapse or cracking during the sintering process, and a higher density is obtained while ensuring structural stability.
[0019] Preferably, the crystal structure of the zinc oxide powder and the crystal structure of the tin oxide powder are both hexagonal.
[0020] When the crystal structure of zinc oxide powder and the crystal structure of tin oxide powder are both hexagonal, a highly dense plastic embryo is formed during the compaction process, which is easy to shape. After it is formed, it is not easy to collapse or crack during the sintering process, and a higher density is obtained while ensuring structural stability.
[0021] Preferably, the molding agent is composed of the following raw materials in parts by weight: Emulsifier 0.1-0.5% Cashew nut shell oil diol 1-3% Cardanol polyoxyethylene ether 0.1-0.8% Guar Hydroxypropyltrimonium Chloride 1-5% The balance is diluent.
[0022] Emulsifier plays the role of emulsification and dispersion. Cashew nut shell oil diol and guar gum hydroxypropyl trimethyl ammonium chloride not only have adhesion, but also have good dispersibility, which can promote the uniformity of zinc oxide powder and tin oxide powder dispersion, and can ensure the stability of the structure during the embryo molding process. Cardanol polyoxyethylene ether, combined with cashew nut shell oil diol and guar gum hydroxypropyl trimethyl ammonium chloride, has better dispersibility, which enables it to be further fully mixed and evenly mixed.
[0023] Preferably, the emulsifier is castor oil polyoxyethylene ether and / or propylene glycol block polyether.
[0024] Castor oil polyoxyethylene ether and / or propylene glycol block polyether are used to achieve better emulsification and suspension effects. Cashew nut shell oil diol, guar gum hydroxypropyltrimethylammonium chloride, and cardanol polyoxyethylene ether are used to further improve the dispersion uniformity of tin oxide powder and zinc oxide powder, and to facilitate filling to form a dense and stable structure.
[0025] Preferably, the diluent is one or more of water, anhydrous ethanol, and propylene glycol methyl ether.
[0026] By using water, anhydrous ethanol, or propylene glycol methyl ether as solvents, the raw material system can be dissolved and fully mixed.
[0027] Preferably, the static pressing molding pressure in step 2 is 140-200 MPa, and the time is 0.5-2 h.
[0028] The above pressure range and time range can form a high-density blank.
[0029] Preferably, the heat treatment process in step 7) is as follows: The calcined embryo is heated to 320-350°C, kept at temperature for 20-30s, and then cooled to 60-70°C at 5-8°C; then heated to 270-290°C, kept at temperature for 50-80s; then cooled to 25-35°C at 10-15°C, and then ground, bound and polished to obtain a TZO target.
[0030] In summary, this application has the following beneficial effects: 1. The present application sequentially undergoes the processes of powder mixing, embryo molding, shaping, sintering, calcining, and heat treatment to form a TZO target with high structural stability and density, and is used in vacuum evaporation to further improve its performance.
[0031] 2. Emulsifier plays the role of emulsification and dispersion. Cashew nut shell oil diol and cashew nut shell oil not only have adhesion, but also have good dispersibility, which can promote the uniformity of zinc oxide powder and tin oxide powder dispersion, and can ensure the stability of the structure during the embryo molding process. Cardanol polyoxyethylene ether, cashew nut shell oil diol and guar gum hydroxypropyl trimethyl ammonium chloride have better dispersibility, which can further enable them to be fully mixed and evenly mixed. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Introduction of some raw materials: Cashew nut shell oil diol, manufacturer Guangzhou Haoyi New Materials Technology Co., Ltd., model FX-9203LP; Cardanol polyoxyethylene ether, manufacturer: Hubei Huada Fine Chemical Co., Ltd., model: BGF-6; Guar gum hydroxypropyltrimonium chloride, manufacturer Jining Sanshi Biotechnology Co., Ltd., model SS-B27; Castor oil polyoxyethylene ether, manufacturer: Jiangsu Hai'an Petrochemical Plant, model EL-40; Propylene glycol block polyether, manufacturer: Jiangsu Hai'an Petrochemical Plant, model L-35. Example
[0034] Example 1 A TZO target sintering molding process is prepared by the following steps: Preparation of the molding agent: According to the percentage by weight, 0.5% of the emulsifier, 0.1% of the cardanol polyoxyethylene ether, 1% of the guar gum hydroxypropyltrimethylammonium chloride and 80% of the water were weighed and mixed evenly to obtain a mixture B1; 3% of the cashew nut shell oil diol was weighed and mixed evenly with 10% of the anhydrous ethanol and 5.4% of the propylene glycol methyl ether to obtain a mixture B2; all the mixtures B1 and B2 were mixed evenly to obtain a molding agent.
[0035] 1) Powder mixing: Weigh zinc oxide powder and tin oxide powder and place them in a stirring device, stir at a speed of 140 r / min for 20 min, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, continue stirring for 20 min, so that the zinc oxide powder, the tin oxide powder and the molding agent are fully mixed to obtain a mixture A; 2) Molding: Place mixture A into a mold and perform static pressure molding at a pressure of 100 MPa for 2 h to obtain a molded embryo; 3) Shaping: The molded embryo with the mold is placed in an oven at 105°C, and the pressure of the embryo is maintained at 30 MPa, and hot pressing is performed for 5 minutes to obtain a shaped embryo; 4) Pre-sintering: Place the shaped embryo with the mold in a sintering furnace, at a temperature of 280°C, keep the pressure of the shaped embryo at 30MPa, perform hot pressing for 30 minutes, and demold to obtain a pre-sintered embryo; 5) Sintering: Place the pre-sintered embryo in a sintering furnace and sinter at 1170°C for 30 minutes to obtain a sintered embryo; 6) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1700°C for 3 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 7) Heat treatment: The calcined embryo is heated to 320°C and kept at this temperature for 30 seconds, and then cooled to 60°C at 5°C; then heated to 290°C and kept at this temperature for 50 seconds; then cooled to 35°C at 10°C, and then ground, bound and polished to obtain a TZO target.
[0036] The weight ratio of zinc oxide powder, tin oxide powder and forming agent in step 1) is 5:5:1; the average particle size of zinc oxide powder and the average particle size of tin oxide powder are both 500nm; the crystal structure of zinc oxide powder is hexagonal, the crystal structure of tin oxide powder is tetragonal, and the emulsifier is castor oil polyoxyethylene ether.
[0037] Example 2 The difference between Example 2 and Example 1 is that the process parameters are different, as follows: 1) Powder mixing: Weigh zinc oxide powder and tin oxide powder and place them in a stirring device, stir them at a speed of 130 r / min for 15 minutes, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, and continue stirring for 25 minutes to fully mix the zinc oxide powder, the tin oxide powder and the molding agent to obtain a mixture A; 2) Molding: Mixture A is placed in a mold and subjected to static pressure molding at a pressure of 180 MPa for 1 h to obtain a molded embryo; 3) Shaping: Put the molded embryo with the mold into an oven at 110°C, keep the pressure of the embryo at 20MPa, and perform hot pressing for 5 minutes to obtain a shaped embryo; 4) Pre-sintering: Place the shaped embryo with the mold in a sintering furnace at a temperature of 300°C, keep the pressure of the shaped embryo at 20MPa, perform hot pressing for 20 minutes, and demold to obtain a pre-sintered embryo; 5) Sintering: Place the pre-sintered embryo in a sintering furnace and sinter at 1180°C for 25 minutes to obtain a sintered embryo; 6) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1750°C for 2.5 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 7) Heat treatment: The calcined embryo is heated to 350°C and kept at this temperature for 25 seconds, and then cooled to 65°C at 7°C; then heated to 280°C and kept at this temperature for 60 seconds; then cooled to 30°C at 13°C, and then ground, bound and polished to obtain a TZO target.
[0038] Example 3 The difference between Example 3 and Example 1 is that the process parameters are different, as follows: 1) Powder mixing: Weigh zinc oxide powder and tin oxide powder and place them in a stirring device, stir them at a speed of 150 r / min for 10 min, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, and continue stirring for 30 min to fully mix the zinc oxide powder, the tin oxide powder and the molding agent to obtain a mixture A; 2) Molding: Mixture A is placed in a mold and subjected to static pressure molding at a pressure of 200 MPa for 0.5 h to obtain a molded embryo; 3) Shaping: The molded embryo with the mold is placed in an oven at 105°C, and the pressure of the embryo is maintained at 30 MPa, and hot pressing is performed for 5 minutes to obtain a shaped embryo; 4) Pre-sintering: Place the shaped embryo with the mold in a sintering furnace, at a temperature of 305°C, keep the pressure of the shaped embryo at 30MPa, perform hot pressing for 30 minutes, and demold to obtain a pre-sintered embryo; 5) Sintering: Place the pre-sintered embryo in a sintering furnace and sinter at 1200°C for 10 minutes to obtain a sintered embryo; 6) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1800°C for 3 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 7) Heat treatment: The calcined embryo is heated to 350°C and kept at this temperature for 20 seconds, and then cooled to 70°C at 8°C; then heated to 270°C and kept at this temperature for 80 seconds; then cooled to 25°C at 15°C, and then ground, bound and polished to obtain a TZO target.
[0039] Example 4 The difference between Example 4 and Example 2 is that the average particle size of the zinc oxide powder and the average particle size of the tin oxide powder are both 300 nm.
[0040] Example 5 The difference between Example 5 and Example 2 is that the average particle size of the zinc oxide powder and the average particle size of the tin oxide powder are both 50 nm.
[0041] Example 6 The difference between Example 6 and Example 4 is that the crystal structure of the zinc oxide powder and the crystal structure of the tin oxide are both hexagonal.
[0042] Example 7 The difference between Example 7 and Example 6 is that the usage ratio of each raw material in the molding agent is different, as follows: Preparation of the molding agent: According to the percentage by weight, 0.3% of the emulsifier, 0.5% of the cardanol polyoxyethylene ether, 3% of the guar gum hydroxypropyltrimethylammonium chloride and 80% of the water were weighed and mixed evenly to obtain a mixture B1; 2% of the cashew nut shell oil diol was weighed and mixed evenly with 10% of the anhydrous ethanol and 4.2% of the propylene glycol methyl ether to obtain a mixture B2; all the mixtures B1 and B2 were mixed evenly to obtain a molding agent.
[0043] Example 8 The difference between Example 8 and Example 6 is that the usage ratio of each raw material in the molding agent is different, as follows: Preparation of the molding agent: According to the percentage by weight, 0.1% of the emulsifier, 0.8% of the cardanol polyoxyethylene ether, 5% of the guar gum hydroxypropyltrimethylammonium chloride and 80% of the water were weighed and mixed evenly to obtain a mixture B1; 1% of the cashew nut shell oil diol was weighed and mixed evenly with 10% of the anhydrous ethanol and 3.1% of the propylene glycol methyl ether to obtain a mixture B2; all the mixtures B1 and B2 were mixed evenly to obtain a molding agent.
[0044] Example 9 The difference between Example 9 and Example 7 is that the emulsifier is composed of castor oil polyoxyethylene ether and propylene glycol block polyether in a weight ratio of 1:1.
[0045] Example 10 The difference between Example 10 and Example 1 is that cashew nut shell oil diol, cardanol polyoxyethylene ether, and guar gum hydroxypropyltrimethylammonium chloride are replaced with pregelatinized starch (Shanghai Guangyuan Chemical Technology Co., Ltd., model 34ff25) in equal amounts.
[0046] Embodiment 11 The difference between Example 11 and Example 1 is that an equal amount of guar gum hydroxypropyltrimethylammonium chloride is replaced by cashew nut shell oil diol.
[0047] Example 12 The difference between Example 12 and Example 1 is that the cashew nut shell oil diol is replaced by guar gum hydroxypropyltrimethylammonium chloride in an equal amount.
[0048] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that there is no step 3), and the specific process is as follows: 1) Powder mixing: Weigh zinc oxide powder and tin oxide powder and place them in a stirring device, stir them at a speed of 140 r / min for 20 min, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, and continue stirring for 20 min to fully mix the zinc oxide powder, the tin oxide powder and the molding agent to obtain a mixture A; 2) Molding: Place mixture A into a mold and perform static pressure molding at a pressure of 100 MPa for 2 h to obtain a molded embryo; 3) Pre-sintering: Place the molded embryo with the mold in a sintering furnace, heat press for 35 minutes at a temperature of 280°C, keep the pressure of the molded embryo at 30MPa, and demold the mold to obtain a pre-sintered embryo; 4) Sintering: Place the pre-sintered embryo in a sintering furnace and sinter at 1170°C for 30 minutes to obtain a sintered embryo; 5) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1700°C for 3 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 6) Heat treatment: heat the calcined embryo to 320℃, keep it warm for 30s, then cool it to 60℃ at 5℃; heat it to 290℃, keep it warm for 50s; cool it to 35℃ at 10℃, grind, bind and polish it to get the TZO target. (The rest are the same) Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that there is no step 4), and the specific process is as follows: 1) Powder mixing: Weigh zinc oxide powder and tin oxide powder and place them in a stirring device, stir them at a speed of 140 r / min for 20 min, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, and continue stirring for 20 min to fully mix the zinc oxide powder, the tin oxide powder and the molding agent to obtain a mixture A; 2) Molding: Place mixture A into a mold and perform static pressure molding at a pressure of 100 MPa for 2 h to obtain a molded embryo; 3) Shaping: The molded embryo with the mold is placed in an oven at 105°C, and the pressure of the molded embryo is maintained at 30 MPa, and hot pressing is performed for 35 minutes to obtain a shaped embryo; 4) Sintering: Place the pre-sintered embryo in a sintering furnace and sinter at 1170°C for 30 minutes to obtain a sintered embryo; 5) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1700°C for 3 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 6) Heat treatment: The calcined embryo is heated to 320°C and kept at this temperature for 30 seconds, and then cooled to 60°C at 5°C; then heated to 290°C and kept at this temperature for 50 seconds; then cooled to 35°C at 10°C, and then ground, bound and polished to obtain a TZO target.
[0049] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that: on the basis of Comparative Example 1, the process of step 1) is different, and the specific process is as follows: 1) Mixing powder: Weigh zinc oxide powder and tin oxide powder and put them into a ball mill with a molding agent, grind for 40 minutes to make the zinc oxide powder, tin oxide powder and molding agent fully mixed, and then put them into an oven at 100°C and dry for 2 hours to obtain a mixture A; 2) Molding: Mixture A is placed in a mold and subjected to static pressure molding at a pressure of 250 MPa for 2 h to obtain a molded embryo; 3) Sintering: Place the molded embryo in a sintering furnace and sinter at a temperature of 1170°C for 30 minutes to obtain a sintered embryo; 4) Calcination: sinter the sintered embryo in a sintering furnace at a temperature of 1700°C for 3 hours, put it into cold water at 20°C, and cool it to 30°C to obtain a calcined embryo; 5) Heat treatment: The calcined embryo is heated to 320°C and kept at this temperature for 30 seconds, and then cooled to 60°C at 5°C; then heated to 290°C and kept at this temperature for 50 seconds; then cooled to 35°C at 10°C, and then ground, bound and polished to obtain a TZO target.
[0050] Performance testing Detection method / test method Experiment (I) Density: Using the Archimedean method, the weight of the TZO target in the air is tested using a balance to obtain the weight M, with an accuracy requirement of ±0.01g; the weight of the target in water is tested using a balance to obtain the weight M2, with an accuracy requirement of ±0.01g; the density calculation formula is: ρ TZO =Mρ 水 / (M-M2).
[0051] Integrity: Observe whether the TZO target has cracks or collapse, and record them; Table 1 Experimental data of Examples 1-12 and Comparative Examples 1-3 Test items <![CDATA[Density (g / cm 3 )]]> Completeness Example 1 6.588 intact Example 2 6.612 intact Example 3 6.552 intact Example 4 6.625 intact Example 5 6.628 intact Example 6 6.848 intact Example 7 6.851 intact Example 8 6.842 intact Example 9 6.881 intact Example 10 6.358 There are cracks Embodiment 11 6.458 There are cracks Example 12 6.399 There are cracks Comparative Example 1 6.114 intact Comparative Example 2 5.835 intact Comparative Example 3 5.668 crack Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that the density of Comparative Examples 1-3 is lower than that of Example 1, and edge cracking occurs in Comparative Example 3. Therefore, it is shown that the higher the density of the TZO target obtained by the preparation method of the present application, the better its physical properties after vacuum evaporation.
[0052] By comparing Example 4 and Example 6 and combining with Table 1, it can be seen that the density of Example 6 is higher, which means that when the crystal structure of zinc oxide powder and the crystal structure of tin oxide are both hexagonal, a higher density can be achieved.
[0053] By comparing Example 1 with Examples 10-12 and combining with Table 1, it can be seen that the density of Examples 10-12 is lower than that of Example 1, and cracks occur, indicating that the emulsifier, cashew nut shell oil diol, cardanol polyoxyethylene ether, and guar gum hydroxypropyltrimethylammonium chloride used in the present application have a synergistic effect, so that the material system is fully mixed and uniform, making it denser during the processing process, and the obtained TZO target has better performance.
[0054] Experiment (II) The TZO targets obtained in Examples 1-12 and Comparative Examples 1-3 were subjected to the following vacuum sputtering coating: TZO target was used as the target material, the sputtering gas was argon, the pressure was 1Pa, the distance from the glass substrate was 10cm, the DC power was 500W, the sputtering time was 5min, the sputtering temperature was 70℃, and a 10-micron TZO target was formed on the substrate. The TZO film was then obtained to test the thermal conductivity.
[0055] Table 2 Experimental data of comparative examples 1-3 of embodiments 1-12 Test items Thermal conductivity (W / (m·K)) Example 1 96.588 Example 2 96.612 Example 3 96.552 Example 4 96.625 Example 5 96.628 Example 6 101.04 Example 7 106.851 Example 8 106.842 Example 9 106.881 Example 10 91.358 Embodiment 11 90.458 Example 12 91.399 Comparative Example 1 93.114 Comparative Example 2 92.835 Comparative Example 3 90.668 By comparing Example 1 with Comparative Examples 1-3, it can be seen that the TZO target of Example 1 has a high density and the obtained thermal conductivity liquid is relatively high, which indicates that the production process of the present application not only forms a high-density TZO target, but also has better conductivity of the vacuum sputtering coating.
[0056] By comparing Example 1 with Examples 10-12 and combining with Table 1, it can be seen that the thermal conductivity of Examples 10-12 is smaller than that of Example 1, indicating that the emulsifier, cashew nut shell oil diol, cardanol polyoxyethylene ether, and guar gum hydroxypropyltrimethylammonium chloride used in the present application play a synergistic role, so that the material system is fully mixed and uniform, making it denser during the processing process, and the thermal conductivity of the obtained TZO target is better.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A TZO target sintering molding process, characterized in that: The following steps are involved: 1) Powder mixing: weigh zinc oxide powder and tin oxide powder according to parts by weight and mix them evenly, then spray a molding agent to fully mix the molding agent with the zinc oxide powder and the tin oxide powder to obtain a mixture A; 2) Molding: subjecting the mixture A to static pressure molding to obtain a molded embryo; 3) Shaping: hot pressing the molded embryo at 105-120°C and a pressure of 10-30MPa to obtain a shaped embryo; 4) Pre-sintering: hot press the shaped embryo at a temperature of 280-305°C for 10-30 minutes, demould, and obtain a pre-sintered embryo; 5) Sintering: pre-sintering the pre-sintered embryo at a temperature of 1170-1200°C for 10-30 minutes to obtain a sintered embryo; 6) Calcination: sintering the sintered embryo at a temperature of 1700-1800°C for 2-3 hours, cooling, and obtaining a calcined embryo; 7) Heat treatment: After the calcined embryo is heat treated, it is ground, bound, and polished to obtain a TZO target.
2. A TZO target sintering molding process according to claim 1, characterized in that: The specific process of step 1) is as follows: weigh zinc oxide powder and tin oxide powder and stir them at a speed of 100-150 r / min for 10-20 minutes, continue stirring, and spray the molding agent on the surface of the zinc oxide powder and the tin oxide powder, and continue stirring for 20-30 minutes to fully mix the zinc oxide powder, tin oxide powder and the molding agent to obtain a mixture A.
3. A TZO target sintering molding process according to claim 1, characterized in that: The weight ratio of zinc oxide powder, tin oxide powder and forming agent in step 1) is (5-10): (5-10):
1.
4. The TZO target sintering molding process according to claim 1, characterized in that: The particle size of the zinc oxide powder and the particle size of the tin oxide powder are both 50-500 nm.
5. The TZO target sintering process according to claim 1, characterized in that: The crystal structure of the zinc oxide powder and the crystal structure of the tin oxide powder are both hexagonal.
6. A TZO target sintering molding process according to claim 1, characterized in that: The molding agent is composed of the following raw materials in parts by weight: Emulsifier 0.1-0.5% Cashew nut shell oil diol 1-3% Cardanol polyoxyethylene ether 0.1-0.8% Guar Hydroxypropyltrimonium Chloride 1-5% The balance is diluent.
7. A TZO target sintering molding process according to claim 5, characterized in that: The emulsifier is castor oil polyoxyethylene ether and / or propylene glycol block polyether.
8. The TZO target sintering process according to claim 5, characterized in that: The diluent is one or more of water, anhydrous ethanol and propylene glycol methyl ether.
9. The TZO target sintering process according to claim 1, characterized in that: The static pressing molding pressure in step 2 is 140-200 MPa, and the time is 0.5-2 h.
10. The TZO target sintering molding process according to claim 1, characterized in that: The heat treatment process of step 7) is as follows: The calcined embryo is heated to 320-350°C, kept at temperature for 20-30s, and then cooled to 60-70°C at 5-8°C; then heated to 270-290°C, kept at temperature for 50-80s; then cooled to 25-35°C at 10-15°C, and then ground, bound and polished to obtain a TZO target.
